2014
DOI: 10.12968/jowc.2014.23.5.259
|View full text |Cite
|
Sign up to set email alerts
|

The use of a specialised amino acid mixture for pressure ulcers: A placebo-controlled trial

Abstract: The use of specialised amino acid does not appear to reduce wound size and PUSH scores but may improve tissue viability after 2 weeks. Further confirmation on a larger scale is required to determine the benefits of supplementing additional HMB, arginine and glutamine in patients with pressure ulcers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 24 publications
2
44
1
4
Order By: Relevance
“…These findings are in line with clinical studies showing a positive effect of nutritional supplementation with additional protein, arginine and micronutrients to promote PU healing [17,18,[22][23][24][25][26][27][28][29][30]. In contrast, the findings of two studies were not in line with the findings of these studies [31,32]. A pragmatic randomised trial showed a significant improvement in wound healing in patients receiving standard nutrition supplement compared to wound-specific supplement, although there was a clinically relevant improvement in quality of life and patient satisfaction in the wound-specific ONS group [31].…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…These findings are in line with clinical studies showing a positive effect of nutritional supplementation with additional protein, arginine and micronutrients to promote PU healing [17,18,[22][23][24][25][26][27][28][29][30]. In contrast, the findings of two studies were not in line with the findings of these studies [31,32]. A pragmatic randomised trial showed a significant improvement in wound healing in patients receiving standard nutrition supplement compared to wound-specific supplement, although there was a clinically relevant improvement in quality of life and patient satisfaction in the wound-specific ONS group [31].…”
Section: Discussionsupporting
confidence: 55%
“…A pragmatic randomised trial showed a significant improvement in wound healing in patients receiving standard nutrition supplement compared to wound-specific supplement, although there was a clinically relevant improvement in quality of life and patient satisfaction in the wound-specific ONS group [31]. The other study, a placebo-controlled randomised controlled trial (RCT), showed that the use of specialised amino acids did not appear to reduce PU wound size [32]. However, the OligoElement Sore Trial (OEST), a level 1 study, confirmed that the additional provision of arginine, zinc, and antioxydants in the nutritional support in malnourished PU patients improved PU healing [33].…”
Section: Discussionmentioning
confidence: 99%
“…The mean age varied from 67.5±4.9 to 81.7±10.7 years and 246 patients participated in the study, 86 (35%) of whom were men and 160 (65%) of whom were women. Of the studies analyzed, one was performed in Australia 14 , one in Singapore 15 and one in Italy 16 . The study by Leigh et al…”
Section: Resultsmentioning
confidence: 99%
“…14 did not receive any type of funding, while the study by Wong et al 15 was supported by Abbot Laboratories Pte Ltd and the authors declared there were no conflicts of interest. Cereda et al 16 received financing from the Azienda Ospedaliera Universitaria Maggiore della Carità and declared that the source of the financial support had no role in the project or the undertaking of the study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation